A tutela coletiva extraprocessual: o diálogo institucional como instrumento de atuação do ministério público para a concretização dos direitos sociais - SILVA, Sandoval Alves da (Universidade Federal do Pará, 2017)
The thesis argues for the progressive implementation of the human rights (gradualist reasoning) via institutional dialogue conducted by the public prosecution service that impacts directly on the „separation of powers” dogma through interaction between the branches of the government. To this end, it resorts to practical examples, theories and normative arguments. The thesis demonstrates the nature of the public prosecution service as a public power with constitutional autonomy and political-bureaucratic capability (democratic and moral legitimacy) to engage in procedural rounds to protect public interest and social demands aiming to fulfill the social rights via political accords that serve as a temporary last word about social conflicts. In order to carry out this task, the institution counts on procedural instruments such as notification, request, recommendation, accords of implementation, etc. Such instruments allow the institution to provoke, initiate, coordinate, conduct and carry out a dialog with the other branches of the government in order to reach a political accord that can fulfill the social rights. This action takes place when the state violates human rights either because it is involved in an excessive activity or because it is in a state of latency due to lack of the necessary specification of the social rights for extrajudicial enforceability and judicial enforceability. Thus, dialogue is integral in cases of default by either violation due to excess or omission of material benefits that are essential to cater for the human needs under the state responsibility in order to meet the immediate continuous and gradual obligation of providing definition, organization, proceduralization, specification and implementation of social rights to ultimately fulfill the distributive justice through the defense of the common, indivisible or collective goods and their individual appropriation scheme.